Values and concerns in decision-making about a waste-reduction incinerator at Stormsriver, Tsitsikamma : a case study in applied ethics - Maharajh, Rajinder Jain (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2003.